Uses and perceptions of Machine Translation at the European Commission - Caroline Rossi; Jean-Pierre Chevrot (JoSTrans: The Journal of Specialised Translation)
Current research on translation technology seeks to integrate physical, cognitive and organisational ergonomics, and uses insights from the situated cognition paradigm to bring together social and technical perspectives on fast-evolving human-computer interactions. Even though these trends imply that a wider variety of professional contexts should be considered, studies of institutional translation are still scarce. This paper reports on a three-week research stay in the French language department of the European Commission (DGT-Fr2), aimed at understanding current uses and perceptions of machine translation (MT) and post-editing within Europe's biggest translation institution. Based on ethnographic data, we established a survey that we tested among French translators before translating it into English and submitting it to all DGT translators. Our quantitative data include 89 respondents from 15 language departments. We perform multiple linear regressions to assess technology acceptance, before focusing on the variance that the model leaves unexplained. Our findings show that perceptions of control, subjective norm and image, as well as insecurity (fear of MT) have an impact on professional MT acceptance.